Conceptual Outlook of the Determinants Influencing the Intention to Adopt Return on Investment Evaluation in Malaysian Manufacturing Small and Medium Enterprises - Luqman Hakim, Satiman; Abdul Halim, Busari; Surena, Sabil; Mohd Sham, Kamis (The Elite Scientific Forum, Pakistan., 2024)
As one of the established methods for evaluating training, return on investment (ROI) is assuming an increasingly vital role in demonstrating that training provides organizations with both monetary and non-monetary benefits. Regrettably, despite ROI’s importance and potential advantages, the implementation of ROI evaluation among Malaysian manufacturing small and medium-sized enterprises (SMEs) is nearly absent. Hence, this study seeks to investigate the factors that influence the intents of Malaysian manufacturing SMEs to adopt ROI training evaluation. Conducting a separate analysis on SMEs is crucial due to their distinctive attributes that set them apart from larger corporations. To accomplish this, the present study defines ROI evaluation as a form of innovation, as it is perceived as new by the organization using it. The determinants that may impact the inclination to adopt ROI evaluation are examined from three perspectives: perceived characteristics of innovation, organizational context, and environmental context. This study aims to enhance the understanding of the factors that can either facilitate or hinder an organization's goal to embrace ROI evaluation. Essentially, this study offers useful insights for HR professionals, government agencies, and policy makers that aim to promote the adoption of ROI measurement in SME firms.